Magneto-optical properties of Mn3+ substituted Fe3O4 nanoparticles. Issue 9 (November 2015) - Güner, S.; Amir, Md.; Geleri, M.; Sertkol, M.; Baykal, A.
Abstract: Mn x Fe3− x O4 (0.0≤ x ≤1.0) nanoparticles were synthesized by the polyol synthesis method and the effect of Mn 3+ substitution on structural, magnetic and optical properties of Fe3 O4 was studied. X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), UV–visible spectroscopy and vibrating sample magnetometer (VSM) were used to study the physical properties. The crystallite (from XRD) and particle sizes (from TEM and SEM) are in close agreement with each other. Lattice parameter increases with increasing Mn 3+ concentration, due to the respective larger ionic radius of Mn 3+ ion compared with the Fe 3+ ion. The magnetic hysteresis ( M – H ) curves revealed superparamagnetic characteristics of the products. The extrapolated specific saturation magnetization ( σ s ) values decreased from maximum value of 47.3 emu/g to the minimum value of 25.6 emu/g by increasing Mn composition. The particle size dependent Langevin function was applied to determine the magnetic particle dimensions ( D mag ) around 15 nm. The observed magnetic moments of NPs are in range of (1.06–1.96) µB and significantly less than 4 µB of bulk Fe3 O4 . Magnetic anisotropy was offered as uniaxial and calculated effective anisotropy constants ( K eff ) are between 34.47×10 4  Erg/g and 21.83×10 4  Erg/g. The size-dependent saturation magnetization suggests the existence of a magnetically inactive layer as 1.638 nm on FeMn x Fe2− x O4 NPs. The UV–vis diffuse reflectance spectroscopy (DRS) and Kubelka−Munk theory were applied to determine the optical properties. The estimated optical band gap ( E g ) values dropped almost linearly from 2.05 eV to 1.17 eV with increasing Mn composition.